2020
DOI: 10.1063/5.0021359
|View full text |Cite
|
Sign up to set email alerts
|

Strain-dependent electronic and optical properties of boron-phosphide and germanium-carbide hetero-bilayer: A first-principles study

Abstract: Opto-electronic properties of boron phosphide–germanium carbide (BP/GeC), a new van der Walls hetero-bilayer (HBL) with all possible stacking patterns, are studied under the density functional theory originated first-principles. The dynamical and chemical stabilities of the hetero-bilayer are confirmed by phonon spectra and binding energy. Among the dynamically stable HBLs, HBL 1 has the lowest binding energy with the smallest interlayer spacing of about 3.442 Å. Both values and natures (indirect or direct) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
3
5
0
Order By: Relevance
“…For GeC monolayer, the lattice constant a is 3.268 Å with a bond length of 1.887 Å [20]. These data are in good correspondent with former studies [26,42,43]. The stacking is made in such a way that the 2 × 2 GeC (a = b = 6.536 Å) monolayer is the bottom layer, and the 2 × 2 planar GaN (a = b = 6.496 Å) is vertically placed on the layer in six different stacking patterns.…”
Section: A Structural Propertiessupporting
confidence: 90%
“…For GeC monolayer, the lattice constant a is 3.268 Å with a bond length of 1.887 Å [20]. These data are in good correspondent with former studies [26,42,43]. The stacking is made in such a way that the 2 × 2 GeC (a = b = 6.536 Å) monolayer is the bottom layer, and the 2 × 2 planar GaN (a = b = 6.496 Å) is vertically placed on the layer in six different stacking patterns.…”
Section: A Structural Propertiessupporting
confidence: 90%
“…In addition, Joseph et al 22 found that changing the rotation angle between layers of the MoS 2 /BP heterostructure, and thus altering the type of band arrangement, can be not only useful for light-emitting diodes but also important for photovoltaic and photocatalytic applications. Khan et al 23 calculated the electron and optical properties of a BP/GaC heterojunction under specific strains by applying different strains, which is of great importance in the field of photovoltaic applications. In contrast to non-metallic materials, Mogulkoc et al 24 utilized black phosphorus and the BP heterostructure.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the GeC based heterobilayers are also extensively studied to tune the electronic properties of the desired heterosystem, i.e. , GeC/GaN, 6 GeC/SiC, 7 GeC/BP, 8 GeC/ZnTe, 9 and GeC/MoS 2 . 10…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The group-IV compound GeC film can be synthesized by various experimental procedures, such as chemical vapor deposition 5 making it compatible with industrial-scale production. Moreover, the GeC based heterobilayers are also extensively studied to tune the electronic properties of the desired heterosystem, i.e., GeC/GaN, 6 GeC/ SiC, 7 GeC/BP, 8 GeC/ZnTe, 9 and GeC/MoS 2 . 10 Recently the intrinsic long range magnetic order in 2D van der Waals crystals has attracted great interest since the experimental synthesis of various 2D magnetic crystals such as chromium trihalides (CrI 3 ), 11 Cr 2 Ge 2 Te 6 12 and Fe 3 GeTe 2 .…”
Section: Introductionmentioning
confidence: 99%